Pemberian Teknik Alih Baring pada Ny. S dengan Gangguan Sistem Kardiovaskular Congestive Heart Failure dengan Masalah Keperawatan Risiko Gangguan Kerusakan Integritas Kulit - Lila Efriyanti Sagala; Afiatika Ahsani (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Congestive Heart Failure is the inability of the heart to pump blood effectively throughout the body. The heart is said to fail not because it stops working, but because it does not pump as hard as it should. One way to reduce the risk of skin integrity disorders is by using the bed transfer technique. This article uses a case study design and the subjects used in this case are Congestive Heart Failure patients treated at RSI Malahayati Medan with nursing problems at risk of skin integrity disorders. The results of the application which had been carried out for 3 days showed different results with the Braden score assessment on the first day getting a score of 12 and the second day getting a score of 14. Conclusion: giving the bed transfer technique can prevent the risk of damage to skin integrity in Congestive Heart Failure patients who experience total bedrest . Suggestions are given to patients to know and carry out bed transfer techniques to prevent the risk of damage to skin integrity.